Interferon-Inducible Protein 16 (IFI16) Has a Broad-Spectrum Binding Ability Against ssDNA Targets: An Evolutionary Hypothesis for Antiretroviral Checkpoint - Hurst, Tara Patricia; Aswad, Amr; Karamitros, Timokratis; Katzourakis, Aris; Smith, Adrian L.; Magiorkinis, Gkikas (Frontiers in Microbiology, 2019)
Human endogenous retroviruses (HERVs) are under genomic and epigenetic control but can be expressed in normal tissues, producing RNA transcripts some of which are translated. While it has not been demonstrated experimentally in modern humans, cDNA copies from HERV RNA (namely HERV-K HML-2 or HK2) were produced after the human-chimp split and until at least 250,000 years ago. We are interested in the hypothesis that such cDNA could be a ligand for pattern recognition receptors (PRRs) of the innate immune response. The AIM-2-like receptors for DNA, interferon--inducible protein 16 (IFI16) and Cyclic GMP-AMP synthase (cGAS) are potential candidate PRRs. IFI16 can detect cDNA produced during HIV-1 replication, causing increased T cell death. While HIV-1 has emerged relatively recently as a human pathogen, the cDNA functionality of IFI16 could have been selected for during the course of human evolution. Here we present a novel hypothesis that the products of reverse transcription of HK2, which has been proliferating in the genome of human ancestors for 30 million years, could interact with IFI16. In support of our hypothesis, we provide preliminary data showing that IFI16 (but not cGAS) interacts with synthetic single-stranded HK2 oligos corresponding to the first product of reverse transcription. ssDNA detection by IFI16 has variability with respect to sequence features, although we find no evidence of dependence on computationally predicted strong secondary structures mimicking dsDNA. Among the HK2 oligos, IFI16 interacts more intensely with those derived from LTRs, suggesting these oligos have undetermined structural features that allow IFI16 to bind with greater affinity. Further, cells with stem cell features that naturally allow HK2 expression were found to express many components of the innate immune system including cGAS but not IFI16. Based on the presented preliminary data we further postulate another hypothesis: that the IFI16 functionality in human cells has been acting as “second-line” defence to control abnormal HK2 replication in somatic tissues. The absence of this protein in stem cells and a stem cell line could permit these cells to express HERVs which contribute to stem cell identity. Finally, we suggest potential studies that could support or refute our hypothesis.